20 transformation years, 1997-2017 - Sreerema Banoo (Universiti Teknologi Petronas, 2016)
Universiti Teknologi PETRONAS is a vibrant habitat enabling life-changing experiences across all areas of teaching, learning and research. Students and faculty are academically and culturally enriched. Over the past 20 years, the UTP campus has transformed into a globally recognised centre of knowledge and education. On the cover, the university's award-winning Chancellor Complex is an amazing monument welcoming eager learners as students and transforming them into market-ready professionals.